Aerobic Oxidative Coupling of Aniline Catalyzed by One-Dimensional Manganese Hydroxide Nanomaterials - Miao, Hui; Ma, Kelong; Hu, Shiwei; Li, Ruiqian; Sun, Lin; Cui, Yumin (Synlett, 2019)
The aerobic oxidative coupling of aniline is an effective process for producing aromatic azo compounds, which are widely used in the organic chemical industry. The development of heterogeneous catalysts for this reaction would be advantageous because of their recyclability and convenience in posttreatment. In this work, one-dimensional Mn(OH)2 nanostructure with various shapes were synthesized through the adjustment of various surfactants. The as-synthesized Mn(OH)2 nanobelts and nanowires showed superior catalytic activity in the activation of oxygen and aniline. Aromatic azo compounds with a variety of substituents were produced through the coupling of the corresponding anilines without additives under ambient conditions.
Keywords: anilines; azo compounds; heterogeneous catalysis; manganese hydroxide; nanobelts; nanowires